’Alma gitana’ & ’Carmen y Lola’: two transversal views towards violence against women in the gypsy ethnic group - López-Cabrales, María del Mar (Comunicación y Género [Communication and Gender], 2019)
This essay analyzes how in two films, Alma gitana (1996) by Chus Gutiérrez, and Carmen and Lola (2018) by Arantxa Echevarría, address and question violence against women in the gypsy community. The two films also call for younger generations to change and build their lives around equality, without totally dismissing the culture or traditions of their ancestors. Both film makers, Chus Gutiérrez and Arantxa Echevarría, are women who do not belong to the gypsy ethnic group but rely on deep knowledge and respect for it, articulate in their films constructive questions to the issue of gender violence in the Roma community.